Nation Formation and Social Cohesion - Maimela, David; Ndletyana, Mcebisi (Book collections on Project MUSE., 2013)
This book critically examines the challenges, successes and failures of the post-1994 South African state against the humane values enshrined in its constitution: non-racial democracy and respect for all generations of human rights: civil, political, social, economic, resources and the environment and gender and communication. The book sheds light on the difficulties faced by the State when trying to bring together a diverse society comprised of traditional South African, Western-based and ''other'' African (immigrant) cultures into a cohesive nation with a common South African identity. The v.